Diversity of Roadside Tree Species in Urban Areas in Southern Zone of Ekiti State, Nigeria - Kayode, J.; Franklin, E.; Ayeni, M. J. (Canadian Journal of Agriculture and Crops, 2016)
An enumeration of roadside trees along major routes of three selected urban towns in southern parts of Ekiti State was examined. A total of 23 tree species belonging to 16 families were enumerated. Tree density enumerated was 147 while houses in the tree vicinities were 442 thus given a ratio of 1 tree to 3 houses. Most of the trees were products of wildling preservation rather than planted. The products derivable from the trees constituted a major prerequisite to their being preserved and/or planted. The incentives and disincentives to tree domestication in the study area were identified. Strategies that would improve the present situation were proposed.